Industrial Scale Bioprocess Simulation for Ganoderma Lucidum Production using Superpro Designer (2020)
The medicinal mushroom Ganoderma lucidum is used by traditional medicine for human infection treatments such as gastric cancer, hypertension, hepatitis, chronic bronchitis and hypocholesterolemia. However, the conventional production of Ganoderma in a solid phase on a large scale is costly and requires excessive processing times, which hinders its technical-economic viability. Based on the preceding, engineering studies are needed to predict their large-scale production, to identify the necessary industrial equipment and costs to propose strategies that reduce operating costs. The SuperPro Designer computational tool is a very versatile simulator used in a wide variety of industrial applications. That is why the purpose of this research is to evaluate the production of the Ganoderma lucidum fungus in large-scale growth culture from a computational approach. The latter, by performing simulations using SuperPro Designer software to identify process yields and propose improvements aimed at increasing productivity. The software was calibrated with experimental data reported from literature and different strategies were intended to determine the economic viability. It was found that the volume of the bioreactor significantly affects production costs compared to exopolysaccharides yields, obtaining values of 6.82 USD/g in a 2 m3 bioreactor while in a production volume of 20 m3 the costs are significantly reduced to 0.8 USD/g. The findings found here demonstrate the importance of predicting a large-scale bioprocess to improve the overall productivity of a biotechnological product.